The effects of the Breathe Right(tm) nasal strip on interval running performance - Case, L.; Redmond, T.; Currey, S.; Wachter, M.; Resh, J. (The Journal of Strength and Conditioning Research, 1998)
The purpose of this research was to determine whether the Breathe Right(tm) nasal strip enhanced performance as measured by maximal ventilation, maximal oxygen uptake, maximal heart rate, and number of repeat intervals completed. Nine male college students (mean age 20.8 ± 2.2 years) ran intervals on a motor-driven treadmill until voluntary exhaustion under 3 conditions: wearing a Breathe Right(tm) nasal strip; wearing a placebo nasal strip; and under a control condition. Expired gases were collected and analyzed on a Beckman metabolic measurement cart. Data were analyzed via repeated measures ANOVA. The alpha level for significance was set at p < 0.05. Repeated measures ANOVA revealed no significant differences in any of the measured variables. Based on this study, it can be concluded that Breathe Right(tm) nasal strips are ineffective in enhancing performance.